Clove Farmers' Efforts to Improve the Family Economy as Part of Children's Education in Skikilale Village, Waplau District, Buru Regency - Nelson Tasidjawa; Louisa M Metekohy; Fatimah Sialana (Journal of Education Technology Information Social Sciences and Health, 2024)
This research aims to find out what efforts are made by farming families to increase clove production in Skikilale village, Waplau District, Buru Regency and the obstacles experienced by farming families in increasing the income of farming families in Sikilale village, Waplau District, Buru Regency. Cloves are one of the main plantation commodities whose role is quite important for the national economy, especially as a provider of employment opportunities, a source of income and foreign exchange. Cloves also play a role in increasing family income which can be used for children's education costs. Skikilale Village is located in a mountainous area with a total of 106 families in the village community, most of whom earn their living as farmers. Workers who work in the agricultural sector earn income which is used to meet living needs and improve household welfare. Research method: descriptive research type, qualitative approach with research subjects numbering 1 to 10 farmers, plus 1 village secretary, 2 Soa heads and village head officials as informants. Hasi; Research shows that the business of clove farmers in meeting children's educational needs is that the reason behind them doing their work as clove farmers is to meet their daily needs, including children's educational needs. Working as clove farmers can fulfill children's educational needs from elementary school to college level. high school and at the tertiary level requires large costs so that you can manage your finances so you can meet your child's educational needs. The obstacles experienced by clove farming families in meeting children's educational needs in Sikilale village, Waplau subdistrict, Buru Regency, are that within the necessities of life there are also children's educational needs and for clove farmers in Sikilale village, children's needs are highly prioritized along with other needs. So there are inhibiting factors in meeting children's needs but these can be resolved by clove farmers themselves by making efforts to fulfill children's educational needs and these efforts are made by clove farmers even if the clove harvest fails.